Lessons learned from youth opportunities united: a successful application for the comprehensive strategy to prevent serious, chronic, and violent juvenile delinquency. - Rhoades, Cecilia; Rhoades, Philip (Facultad de Trabajo Social y Desarrollo Humano, 2008)
The article examines a strategy known as Youth Opportunities United (YOU) developed in Corpus Christi, Texas. It is a voluntary collaboration of multiple agencies and individuals interested in reducing juvenile delinquency through programs focused on prevention, intervention, sanctioned care for adjudicated juvenile delinquents and aftercare of those juveniles released from sanctioned situations.